Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Robot-assisted Neural Radiance fields for plot-level cotton crop 3D reconstruction and yield estimation - Lizhi Jiang; Peng W. Chee; Changying Li; Longsheng Fu (Computers and Electronics in Agriculture, 2026)

Insight into oxygen vacancies roles and reaction mechanism of PMoA-TiO2-M catalyst on deep oxidative desulfurization of fuel oil - Jiyuan Fan; Tairan Wang; Peng Liu; Abdul-Hamid Emwas; Vasileios G. Samaras; Javier Ruiz-Martinez; Chee Kok Poh; Jie Chang; William L. Roberts (Fuel, 2026)

Energy efficiency in chemo-mechanical pretreatment of oil palm biomass: Sequence analysis and process optimization for enhanced bioethanol production - Yitong Niu; Kamoldeen Abiodun Ajijolakewu; Chee Keong Lee; Cheu Peng Leh (Biomass and Bioenergy, 2026)

A review of visual navigation for agricultural robots in open fields and controlled environments - Rui-Feng Wang; Rui Xu; Peng W. Chee; Haihua Wang; Changying Li (Computers and Electronics in Agriculture, 2026)

3D geological model-based coupled modeling method for braced excavation integrated with adjacent buildings and its application to monitoring scheme optimization - Cong Zhou; Bin Xiang; Lei He; Junchen He; Luyuan Peng; Zhiting Jiang; Chee Kiong Soh (Bulletin of Engineering Geology and the Environment, 2026)

Plastic substrates shape prokaryotic community structure and resistance gene assemblages in tropical coastal waters - Emily Curren; Lay Peng Lim; Sandric Chee Yew Leong (Environmental Science and Pollution Research, 2026)

Land use and soil texture drive shifts in communities of soil biota across natural and anthropogenic tropical ecosystems - Umar Hussaini Tarmizi; Farhana Adilah Zahari; Amirah Alias; Seng Chee Poh; Wei San Phang; Kai Yue; Yan Peng; Siti Norasikin Ismail; Xiangzhen Li; Haris Hafizal Abd Hamid; Mohamad Aqmal-Naser; Alexandre Soares Rosado; et al. (European Journal of Soil Biology, 2026)

Traversing the Valley of Death for nanotechnology-based natural products: strategies and insights from pharmaceutical stakeholders - Jian Sheng Loh; Chan Yew Low; Wei Peng Low; Yun Lin Ng; Wen Qi Mak; Li Kar Stella Tan; Hong Hao Chan; Yong Sze Ong; Stephanie Kay Ann Cheah; Emmellie Laura Albert; Chee Wun How (Drug Delivery and Translational Research, 2025)

Genetic basis and role of exotic accessions in cultivated cotton fiber quality improvement - Ankush Sharma; Mingrui Xu; Deepak Vitrakoti; Jinesh D. Patel; Peng W. Chee; Andrew H. Paterson (Theoretical and Applied Genetics, 2025)
Key message Exotic Gossypium accessions still harbor QTL‑validated alleles that, combined with CRISPR pyramiding and genomic selection, can break the entrenched fiber length–strength trade‑off. Abstract Cotton’s four independent domestications twice in diploids and twice in allotetraploids offer a natural experiment in fiber improvement. Synthesizing three decades of data, we chart how polyploidy, selection and modern breeding have repeatedly reshaped the Gossypium genome. More than 15,000 quantitative trait locus (QTL) and genome wide association mapping studies (GWAS) hits converge on a handful of chromosomal “hotspots”; new MAGIC, NAM, NIL and long-read resources now narrow these peaks to < 200 kb, resolving causal genes such as GhHOX3, GhZF14 and GhMYB7 . Multi-omics evidence links auxin, ethylene, gibberellin, brassinosteroid and strigolactone signaling to HDZIP IV, MYB, bHLH/HLH and ERF networks that drive fiber initiation, extreme cell elongation and cellulose deposition. Population genomics shows that ~ 40% of favorable fiber alleles are fixed in elite Gossypium hirsutum , yet wild diploids and landraces still harbor variants that could break the length strength trade-off. We propose a three-step roadmap genomic selection, CRISPR gene pyramiding and accelerated introgression to expand cotton’s genetic base and deliver fibers suited to sustainable textile demands.

Cotton3DGaussians: Multiview 3D Gaussian Splatting for boll mapping and plant architecture analysis - Lizhi Jiang; Jin Sun; Peng W. Chee; Changying Li; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Genetic dissection of lint percentage and seed cotton yield in exotic x elite upland cotton crosses using population-specific and joint population analysis - Hrithik Mangla; Min Liu; Deepak Vitrakoti; Tariq Shehzad; Rahul Chandnani; Sayan Das; Jason G. Wallace; John L. Snider; Don C. Jones; Peng W. Chee; Andrew H. Paterson (Euphytica, 2025)
Limited genetic diversity for fiber quality and yield traits in the improved gene pool for Upland cotton motivates the exploration of exotic materials. In the present study, we carried out QTL mapping for 2 fiber yield components in five BC 1 F 2 and one F 3 resembling intermated population(s) involving 5 ‘converted’ exotic lines of Upland cotton and an elite cultivar “DES56,” as a common parent in all populations. The results indicated a higher frequency of dominant QTLs than additive QTLs. However, the prevalence of negative heterotic effects shows few opportunities to utilize these exotic lines for hybrid production. Most of the dominant QTLs were overdominant. In addition, all additive QTLs for lint percentage indicated the DES56 allele to be superior. These results suggest that selection practices need to be carried out in the later generations along with the implementation of precise marker-assisted selection to avoid the undesirable heterotic effects of these regions and reduce the linkage drag from undesirable alleles in the exotic segments. Moreover, the population-specific analysis and joint analysis showed the inflation of QTL parameters with a decrease in sample size, indicating the importance of larger sample sizes in mapping populations. Overall, the potential for using these exotic race stocks for hybrid production targeting yield components is limited.

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Sustainable biological production and innovative purification of the 1,3-propanediol from glycerol fermentation broth via resin adsorption - Amer Aref Said Ismail; Yuana Elly Agustin; Teck Ann Yeow; Fang Baishan; Nur Syakina Jamali; Swee Keong Yeap; Hemavathi Silvamany; Tan Peng Chee; Tan Jian Ping (Food and Bioproducts Processing, 2025)

An intelligent resilience evaluation model for the development of urban underground space with safety concern of surrounding existing built environment - Cong Zhou; Yanqi Su; Lei He; Luyuan Peng; Yi Zhang; Gang Wu; Chee Kiong Soh (Tunnelling and Underground Space Technology, 2024)

Elucidating the Correlation of Lignocellulosic Compositions and Physicochemical Alterations in Oil Palm (Elaeis guineensis) Biomass on Enzymatic Saccharification Yield - Tannimalay Hemashini; Chee Keong Lee; Choon Fu Goh; Ying Ying Tye; Maya Ismayati; Yin Ying H’ng; Cheu Peng Leh (BioEnergy Research, 2024)

An analysis of lncRNAs related to fiber quality and the discovery of their target genes in a Gossypium hirsutum line with Gossypium mustelinum introgression - Baohua Wang; Meijun Ji; Hui Fang; Haijing Gu; Teame Gereziher Mehari; Jinlei Han; Wenxiang Feng; Xuehan Huo; Jingxia Zhang; Yu Chen; Jun Zhang; Allah Ditta; et al. (Theoretical and Applied Genetics, 2024)

Comparative genomic and phenotypic analyses of pathogenic fungi Neoscytalidium dimidiatum and Bipolaris papendorfii isolated from human skin scraping - Chee Sian Kuan; Kee Peng Ng; Su Mei Yew; Hadiza Umar Meleh; Heng Fong Seow; Kang Nien How; Siok Koon Yeo; Jap Meng Jee; Yung-Chie Tan; Wai-Yan Yee; Chee-Choong Hoh; Rukumani Devi Velayuthan; et al. (Brazilian Journal of Microbiology, 2023)

Genomic structure of the native inhabitants of Peninsular Malaysia and North Borneo suggests complex human population history in Southeast Asia - Chee-Wei Yew; Dongsheng Lu; Lian Deng; Lai-Ping Wong; Rick Twee-Hee Ong; Yan Lu; Xiaoji Wang; Yushimah Yunus; Farhang Aghakhanian; Siti Shuhada Mokhtar; Mohammad Zahirul Hoque; Christopher Lok-Yung Voo; et al. (Human Genetics, 2018)

Comparative genetic variation of fiber quality traits in reciprocal advanced backcross populations - Rahul Chandnani; Zhengsheng Zhang; Jinesh D. Patel; Jeevan Adhikari; Sameer Khanal; Daohua He; Nino Brown; Peng W. Chee; Andrew H. Paterson (Euphytica, 2017)

Segregation distortion and genome-wide digenic interactions affect transmission of introgressed chromatin from wild cotton species - Rahul Chandnani; Baohua Wang; Xavier Draye; Lisa K. Rainville; Susan Auckland; Zhimin Zhuang; Edward L. Lubbers; O. Lloyd May; Peng W. Chee; Andrew H. Paterson (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qFL-chr1, a fiber length QTL in cotton - Peng Xu; Jin Gao; Zhibin Cao; Peng W. Chee; Qi Guo; Zhenzhen Xu; Andrew H. Paterson; Xianggui Zhang; Xinlian Shen (Theoretical and Applied Genetics, 2017)

QTL analysis of cotton fiber length in advanced backcross populations derived from a cross between Gossypium hirsutum and G. mustelinum - Baohua Wang; Xavier Draye; Zhimin Zhuang; Zhengsheng Zhang; Min Liu; Edward L. Lubbers; Don Jones; O. Lloyd May; Andrew H. Paterson; Peng W. Chee (Theoretical and Applied Genetics, 2017)

Re-evaluation of the inheritance for root-knot nematode resistance in the Upland cotton germplasm line M-120 RNR revealed two epistatic QTLs conferring resistance - Yajun He; Pawan Kumar; Xinlian Shen; Richard F. Davis; Guillermo Van Becelaere; O. Lloyd May; Robert L. Nichols; Peng W. Chee (Theoretical and Applied Genetics, 2014)

Promising outcomes in glutaric aciduria type I patients detected by newborn screening - Chee-Seng Lee; Yin-Hsiu Chien; Shinn-Forng Peng; Pin-Wen Cheng; Lih-Maan Chang; Ai-Chu Huang; Wuh-Liang Hwu; Ni-Chung Lee (Metabolic Brain Disease, 2013)

Development of a core set of SSR markers for the characterization of Gossypium germplasm - John Z. Yu; David D. Fang; Russell J. Kohel; Mauricio Ulloa; Lori L. Hinze; Richard G. Percy; Jinfa Zhang; Peng Chee; Brian E. Scheffler; Don C. Jones (Euphytica, 2012)
Molecular markers such as simple sequence repeats (SSR) are a useful tool for characterizing genetic diversity of Gossypium germplasm. Genetic profiles by DNA fingerprinting of cotton accessions can only be compared among different collections if a common set of molecular markers are used by different laboratories and/or research projects. Herein, we propose and report a core set of 105 SSR markers with wide genome coverage of at least four evenly distributed markers per chromosome for the 26 tetraploid cotton chromosomes. The core marker set represents the efforts of ten research groups involved in marker development, and have been systematically evaluated for DNA polymorphism on the 12 genotypes belonging to six Gossypium species [known collectively as the cotton marker database (CMD) panel]. A total of 35 marker bins in triplex sets were arranged from the 105 markers that were each labeled with one of the three fluorescent dyes (FAM, HEX, and NED). Results from this study indicated that the core marker set was robust in revealing DNA polymorphism either between and within species. Average value of polymorphism information content (PIC) among the CMD panel was 0.65, and that within the cultivated cotton species Gossypium hirsutum was 0.29. Based on the similarity matrix and phylogenetic analysis of the CMD panel, the core marker set appeared to be sufficient in characterizing the diversity within G . hirsutum and other Gossypium species. The portability of this core marker set would facilitate the systematic characterization and the simultaneous comparison among various research efforts involved in genetic diversity analysis and germplasm resource preservation.

QTL alleles for improved fiber quality from a wild Hawaiian cotton, Gossypium tomentosum - Zhengsheng Zhang; Junkang Rong; Vijay N. Waghmare; Peng W. Chee; O. Lloyd May; Robert J. Wright; John R. Gannaway; Andrew H. Paterson (Theoretical and Applied Genetics, 2011)

Bilateral anterior uveitis secondary to erlotinib - Lik Thai Lim; Robert Alexander Blum; Chee Peng Cheng; Abdul Hanifudin (European Journal of Clinical Pharmacology, 2010)

Fine mapping QMi-C11 a major QTL controlling root-knot nematodes resistance in Upland cotton - Xinlian Shen; Yajun He; Edward L. Lubbers; Richard F. Davis; Robert L. Nichols; Peng W. Chee (Theoretical and Applied Genetics, 2010)

Sequencing and Utilization of the Gossypium Genomes - Andrew H. Paterson; Jun-kang Rong; Alan R. Gingle; Peng W. Chee; Elizabeth S. Dennis; Danny Llewellyn; Leon S. Dure; Candace Haigler; Gerald O. Myers; Daniel G. Peterson; Mehboob ur Rahman; Yusuf Zafar; et al. (Tropical Plant Biology, 2010)

Molecular and cellular mechanisms of anthracycline cardiotoxicity - Billy Chen; Xuyang Peng; Laura Pentassuglia; Chee Chew Lim; Douglas B. Sawyer (Cardiovascular Toxicology, 2007)

QTL mapping for resistance to root-knot nematodes in the M-120 RNR Upland cotton line (Gossypium hirsutum L.) of the Auburn 623 RNR source - Xinlian Shen; Guillermo Van Becelaere; Pawan Kumar; Richard F. Davis; O. Lloyd May; Peng Chee (Theoretical and Applied Genetics, 2006)

Genetic mapping and comparative analysis of seven mutants related to seed fiber development in cotton - Junkang Rong; Gary J. Pierce; Vijay N. Waghmare; Carl J. Rogers; Aparna Desai; Peng W. Chee; O. Lloyd May; John R. Gannaway; Jonathan F. Wendel; Thea A. Wilkins; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Molecular dissection of interspecific variation between Gossypium hirsutum and G. barbadense (cotton) by a backcross-self approach: II. Fiber fineness - Xavier Draye; Peng Chee; Chun-Xiao Jiang; Laura Decanini; Terrye A. Delmonte; Robert Bredhauer; C. Wayne Smith; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Molecular dissection of interspecific variation between Gossypium hirsutum and Gossypium barbadense (cotton) by a backcross-self approach: I. Fiber elongation - Peng Chee; Xavier Draye; Chun-Xiao Jiang; Laura Decanini; Terrye A. Delmonte; Robert Bredhauer; C. Wayne Smith; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Molecular dissection of phenotypic variation between Gossypium hirsutum and Gossypium barbadense (cotton) by a backcross-self approach: III. Fiber length - Peng W. Chee; Xavier Draye; Chun-Xiao Jiang; Laura Decanini; Terrie A. Delmonte; Robert Bredhauer; C. Wayne Smith; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Putrescine enhances somatic embryogenesis and plant regeneration in upland cotton - Hamidou F. Sakhanokho; Peggy Ozias-Akins; O. Lloyd. May; Peng W. Chee (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Detection of insect Juvenile hormone III and Its precursors fromin Vitro plantlets ofCyperus aromaticus - Chan Chee Weng; Chan Lai Keng; Boey Peng Lim (Journal of Plant Biology, 2004)

Somatic embryo initiation and germination in diploid cotton (Gossypium arboreum L.) - Hamidou F. Sakhanokho; Allan Zipf; Kanniah Rajasekaran; Sukumar Saha; Govind C. Sharma; Peng W. Chee (In Vitro Cellular & Developmental Biology - Plant, 2004)

Use of Artificial Neural Networks to Predict Drug Dissolution Profiles and Evaluation of Network Performance Using Similarity Factor - Kok Khiang Peh; Chee Peng Lim; Siow San Quek; Kean Hock Khoh (Pharmaceutical Research, 2000)